Variability of Sea Surface Temperature and Salinity during Super El Nino 2015 and Strong La Nina 2022 in Southern Java Waters - Agitha Saverti Jasmine; Erik Munandar (Politeknik Negeri Batam, 2026)
The southern waters of Banten and West Java constitute a seasonal coastal upwelling pathway that is highly sensitive to global climate variability. This study aims to analyze and compare the spatial-temporal patterns of sea surface temperature (SST) and sea surface salinity (SSS) during two contrasting climate extremes: the Super El Niño (2015) and the Triple-Dip La Niña (2022). Daily gridded data with a spatial resolution from the Copernicus Marine Service (CMS) were processed via cloud computing using the Xarray, Matplotlib, and Cartopy libraries. The results demonstrate a pronounced interannual contrast during the Southeast Monsoon (July-October). At the peak of El Niño (September 2015), an intensification of robust upwelling occurred, characterized by an extreme drop in minimum SST to 22–24°C and a sharp increase in SSS to 33.8–34.5 psu, driven by reduced freshwater flux and the displacement of deep, saline water masses. Otherwise, during the La Niña phase (2022), upwelling weakened significantly; SST remained warm, ranging from 27-28°C (4-5°C warmer than in 2015), while SSS remained low at 32.6–33.4 psu due to enhanced precipitation and freshwater transport through the Sunda Strait and the Indonesian Throughflow (ITF) circulation. These dynamics underscore the pivotal role of ENSO teleconnections and monsoonal winds in modulating the variability within the study area.